Acyclic and Cyclic Alkyl and Ether‐Functionalised Sulfonium Ionic Liquids Based on the [TFSI]− and [FSI]− Anions as Potential Electrolytes for Electrochemical Applications. Issue 23 (23rd October 2018) - Murphy, Sinead; Ivol, Flavien; Neale, Alex R.; Goodrich, Peter; Ghamouss, Fouad; Hardacre, Christopher; Jacquemin, Johan
Abstract: This work provides a study based on acyclic and cyclic sulfonium ionic liquids (ILs) with alkyl and ether‐functionality on the cation paired with the bis(trifluoromethyl)sulfonylimide, [TFSI] −, or the bis(fluorosulfonyl)imide, [FSI] −, as the counter anion. Herein, thermophysical characterisation of nine sulfonium‐based ILs concerning the density, viscosity and conductivity and thermal properties including phase transition behaviour and decomposition temperature is reported. The electrochemical stability of the ILs was also measured by cyclic voltammetry at a glassy carbon macro‐disk electrode. All of the ILs showed low melting point, low viscosity and good conductivity and could serve as potential electrolytes for energy storage devices. Abstract : The synthesis, purification and characterization of acyclic and cyclic sulfonium ionic liquids (ILs) with alkyl and ether‐functionality on the cation paired with the bis(trifluoromethyl)sulfonylimide or the bis(fluorosulfonyl)imide counter anion are reported. All the ILs showed interesting properties (such as low melting point, low viscosity, and good conductivity) and could be considered as potential electrolytes for energy‐storage devices.